Beyond Eye Care – Low Vision Rehabilitation of a Patient with Recent-Onset Leber’s Hereditary Optic Neuropathy: A Case Report - Poon, Teresa; Labreche, T. (Canadian Journal of Optometry, 2014)
Leber’s hereditary optic neuropathy (LHON) is a maternally inherited mitochondrial deoxyribonucleic acid (DNA) mutation that results in painless, sudden-onset, bilateral central vision loss and dyschromatopsia. Currently, there are no proven treatments to prevent or reverse the optic neuropathy in LHON. Accordingly, individualized rehabilitation services and assistive devices for low vision are crucial for helping people with LHON to regain independence and quality of life. This report describes the impact of multidisciplinary low vision rehabilitation on a young man with recent-onset LHON and emphasizes the importance of the provision of emotional support through counselling for low vision.